Maneuvering towards adaptive co-management in a coral reef fishery. (December 2018) - Hunter, Chelsea E.; Lauer, Matthew; Levine, Arielle; Holbrook, Sally; Rassweiler, Andrew
Abstract: Tropical coral reef ecosystems in the Pacific region are degrading rapidly as ocean temperatures rise and local anthropogenic stressors increase. In this context of rapid change, effective site-based management of coral reef fisheries necessitates flexible environmental governance that is closely attuned to the needs of multiple stakeholders who depend on the fishery for income, food, and cultural identity. As such, many practitioners and scholars call for adaptive co-management of coral reef fisheries where local resource users play a primary role in environmental governance with the support of flexible institutions that operate across organizational scales. This article describes the history and evaluates the current status of marine governance in Moorea, French Polynesia. Established in 2004, the management framework is under revision because it has failed to meet its ecological objectives and has generated discontent among many stakeholders. Drawing on household surveys, interviews, and archival information, the challenges to as well as the factors that may enable a more successful transition of the current governance arrangement towards co-management are detailed. It is argued that recent social mobilization, subsistence and cultural links to the fishery, the presence of geographically and socially relevant traditional governance boundaries, and the implementation of co-management in other parts of French Polynesia are positive factors. However, lack of trust between stakeholders, social heterogeneity, disruption of traditional cultural institutions and practices, minimal institutional support, and an uncertain legal framework suggest that there are significant headwinds for maneuvering towards successful co-management in Moorea. Highlights: Conflicts led to social mobilization and demands for environmental governance changes. Some Mooreans have organized around rahui, a traditional management arrangement. Appropriate and established inter-island governance boundaries enable co-management. Lack of trust between stakeholders is a major hindrance. Presence of coral reef research centers present challenges and opportunities.